2020
DOI: 10.1371/journal.ppat.1008281
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of a Gram-positive Pel polysaccharide biosynthetic gene cluster

Abstract: Our understanding of the biofilm matrix components utilized by Gram-positive bacteria, and the signalling pathways that regulate their production are largely unknown. In a companion study, we developed a computational pipeline for the unbiased identification of homologous bacterial operons and applied this algorithm to the analysis of synthase-dependent exopolysaccharide biosynthetic systems. Here, we explore the finding that many species of Grampositive bacteria have operons with similarity to the Pseudomonas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 70 publications
0
48
2
Order By: Relevance
“…Pel, like GAG, is a partially de-N-acetylated GalNAc-rich polymer involved in biofilm formation in some P. aeruginosa strains [55][56][57][58] . Pel operons have been found in Proteobacteria, including Burkholderia and Moritella species 59 and more recently in a wide range of Gram-positive bacteria 60,61 , suggesting that many bacteria produce a Pel/GAG-like polymer.…”
Section: Agd3 Contains a Unique Carbohydrate Binding Module (Cbm)mentioning
confidence: 99%
“…Pel, like GAG, is a partially de-N-acetylated GalNAc-rich polymer involved in biofilm formation in some P. aeruginosa strains [55][56][57][58] . Pel operons have been found in Proteobacteria, including Burkholderia and Moritella species 59 and more recently in a wide range of Gram-positive bacteria 60,61 , suggesting that many bacteria produce a Pel/GAG-like polymer.…”
Section: Agd3 Contains a Unique Carbohydrate Binding Module (Cbm)mentioning
confidence: 99%
“…It is unclear what the function of this domain is in the context of Pel biosynthesis, although we hypothesize that it may mediate interactions with membrane-embedded Pel components to keep it associated with active polymer production, similar to the interaction between PelA and PelB in Gram-negatives. 16 Curiously, we noted that while all Gram-positive PelA orthologs lack a glycoside hydrolase domain, many of the associated biosynthetic clusters, including B. cereus, 11 contain a separate gene with predicted similarity to the glycoside hydrolase domain found in P. aeruginosa PelA. 15 Our analyses have confirmed that this protein is an active α-1,4-N-acetyl-galactosaminidase and revealed that deletion of this gene significantly elevated biofilm formation.…”
Section: Similar But Different: Gram-positive Pela Is a Mono-functionmentioning
confidence: 57%
“…11,18 While this domain is enzymatically inactive, an allosteric product inhibition site retains the ability to bind c-di-GMP, which is required for Pel production in P. aeruginosa and B. cereus. 11,18 We found that in Streptococci the GGDEF domain of PelD is universally absent which, combined with the lack of genomically-encoded c-di-GMP metabolic enzymes, suggests that Pel production is unlikely to be regulated post-translationally by c-di-GMP in this genus (Figure 3). 11 Instead, Streptococci have several additional genes of unknown function directly downstream of pelG that appear to be part of the same operon, which may provide a means to regulate Pel biosynthesis using an as yet undiscovered mechanism.…”
Section: C-di-gmp Is Not Universal: Adapting Post-translational Regulmentioning
confidence: 99%
“…On the other hand, a recent study by Whitfield et al [32] suggests that the polysaccharide Pel is essential for the biofilm formation of B. cereus ATCC 10987.…”
Section: Discussionmentioning
confidence: 97%
“…The cellulase-sensitive properties of strains ATCC 10987 and BC4 suggest that cellulose may play an essential role in their biofilm formation (Fig 2). On the other hand, a recent study by Whitfield et al [32] suggests that the polysaccharide Pel is essential for the biofilm formation of B. cereus ATCC 10987. Considering that Pel is also cellulase-sensitive [33], the degradation of Pel by cellulase may have occurred in strain ATCC 10987, inhibiting its biofilm formation.…”
Section: Discussionmentioning
confidence: 99%